Synthesis and properties of chiral amide-bonded porphyrin dimers with various functional bridging blocks. (December 2019) - Zhu, Weihua; Najeeb-uz-Zaman Haider, Syed; Zhang, Honglin; Attatsi, Isaac Kwaku; Mack, John; Dingiswayo, Somila; Nyokong, Tebello; Song, Yuting; Xu, Haijun; Liang, Xu
Abstract: Eight porphyrin dimers with various functional bridging blocks and chiral amide-bonds were synthesized and characterized. An analysis of the spectroscopy and electrochemistry has been carried out to demonstrate that the chiral properties can be modified by changing the interchromophoric through-space coupling distance between the two porphyrin chromophores by introducing various bonding and bridging blocks. Highlights: Eight amide-bonded chiral porphyrin dimers were synthesized and characterized. Electronic structure was investigated by spectroscopy and electrochemistry. The molecular chirality can be modified by changing the interchromophoric through-space interactions.